Enhancing Student Satisfaction Through Service Excellence in Higher Education Administration: A Qualitative Case Study - Muhammad Wahyu Ariyanto; M Fahmi Zakariyah; Hafis Muaddab; Khudrotun Nafisah (Journal of Office Administration : Education and Practice, 2026)
This study explores service excellence strategies in improving the quality of educational administrative services to support student satisfaction at Universitas Negeri Surabaya. Using a qualitative case study approach, data were collected through in-depth interviews, direct observation, and document analysis involving administrative leaders, administrative staff, and students. The findings reveal that service quality improvement is implemented through several strategic dimensions, including service responsiveness, administrative standardization, staff professionalism, complaint management optimization, and digital transformation. These strategies contribute significantly to improving administrative efficiency, communication transparency, institutional trust, and students’ overall service experiences. The study further demonstrates that student satisfaction is influenced not only by procedural outcomes but also by interpersonal interactions such as empathy, responsiveness, and staff willingness to provide assistance. In addition, the findings indicate that challenges in service quality improvement include resistance to organizational change, limited human resources, inconsistent inter-unit coordination, and infrastructure constraints. The study reinforces the relevance of service excellence and SERVQUAL perspectives in higher education administration while highlighting the importance of sustainable institutional commitment, digital governance, and student-centered service culture. This research provides practical insights for higher education institutions in developing effective administrative service improvement strategies to strengthen educational quality and institutional competitiveness.